PENGARUH PEMBERIAN BANTUAN PROGRAM KELUARGA HARAPAN (PKH) TERHADAP KESEJAHTERAAN MASYARAKAT : (Studi Kasus: Pemberdayaan Ekonomi Masyarakat Rw. 26 Kelurahan Baktijaya Kec. Sukamjaya Kota Depok) - Arum, Dewi Sekar; Digdowiseiso, Kumba (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Abstract. The research aims to examine the effect of providing assistance with the Hope Family Program (PKH) on community welfare. The research was conducted at Community RW.26 Kelurahan Baktijaya Kecamatan Sukmajaya, Depok City Which received assistance from the Family Hope Program (PKH). The research method used is quantitative methods with a sampling Technique of the number of informants 17 beneficary families of the family hope program assistance. Data Collection techniques used by observation, interviews and documentation. The data analysis Technique is using simple linear regression method. The result showed that PKH implementation had an effect on people’s welfare